Precarious Territory: Property Law, Housing, and the Socio‐Spatial Order. Issue 1 (30th September 2019) - Blomley, Nicholas
Abstract: Most of us access shelter over land over which other people have legally sanctioned dominant interests and powers, creating systemic relations of security and vulnerability that I term precarious property. We all live inside the territory of property, but do so under different terms. Rather than thinking of the territory of property as an exclusive space of insiders and outsiders, I think of it as a relational technology that organises forms of conditional spatial access. Territorialised expressions of law play a crucial role in organising such relations through a "property space" that frames property's participants, their interactions, their alternatives to transacting, and the meanings of property itself. Thinking territorially about precarious property offers us both analytical and ethico‐political insights, I suggest.